2012
DOI: 10.1128/aem.00246-12
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Estimation of the Viability of Toxoplasma gondii Oocysts in Soil

Abstract: ABSTRACTToxoplasma gondiioocysts spread in the environment are an important source of toxoplasmosis for humans and animal species. Although the life expectancy of oocysts has been studied through the infectivity of inoculated soil samples, the survival dynamics of oocysts in the environment are poorly documented. The aim of this study was to quantify oocyst viability in soil over time under two rain condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 24 publications
4
74
0
3
Order By: Relevance
“…Interannual variability in seroprevalence as a function of yearly rainfall and temperature has also been described in two other roe deer populations in France (Gotteland et al 2014). These results thus confirm previous observations, indicating that the survival of oocysts, and thus the contact between roe deer and infectious T. gondii, is highest during wet years with mild winters (Lélu et al 2012). In addition, we showed that an increase in the proportion of the area covered by human dwellings within the individual roe deer's home range was associated with increased T. gondii apparent seroprevalence.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Interannual variability in seroprevalence as a function of yearly rainfall and temperature has also been described in two other roe deer populations in France (Gotteland et al 2014). These results thus confirm previous observations, indicating that the survival of oocysts, and thus the contact between roe deer and infectious T. gondii, is highest during wet years with mild winters (Lélu et al 2012). In addition, we showed that an increase in the proportion of the area covered by human dwellings within the individual roe deer's home range was associated with increased T. gondii apparent seroprevalence.…”
Section: Discussionsupporting
confidence: 88%
“…It spreads in the environment through the feces of Felidae (especially domestic and wild cats) which are the definitive hosts (Dubey 2009). The free-living stages (oocysts) may survive up to 2 years and are disseminated in soil and water, where their survival is sensitive to climatic conditions (Lélu et al 2012). Mild winters with early springs and high humidity favor oocyst survival and sporulation, which is necessary for infection (Gamarra et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We also tested the NAO value for year N -1 to analyze the influence of past climate variations. We expected the risk of toxoplasmosis to be the highest either during cool years or during warm and moist years (Frenkel et al 1975, Dumètre and Dardé 2003, Lélu et al 2012). …”
Section: Meteorological Datamentioning
confidence: 99%
“…The environment is more conducive to extended viability of the environmentally resistant, highly infective oocyst stage in this region [29]. Further, behavioral factors such as agricultural activity may represent an additional explanation for this comparatively high prevalence.…”
Section: Use Of the Truven Health Marketscan Commercial Claims Andmentioning
confidence: 99%